Foliar Application of an Inositol-Based Plant Biostimulant Boosts Zinc Accumulation in Wheat Grains: A μ-X-Ray Fluorescence Case Study - Amaral, Douglas C.; Brown, Patrick H. (Frontiers in Plant Science, 2022)
There has been much interest in the incorporation of organic molecules or biostimulants into foliar fertilizers with the rationalization that these compounds will enhance the uptake, or subsequent mobility of the applied nutrient. The objective of this research was to investigate the effects of an inositol-based plant stimulant on the mobility and accumulation of foliar-applied zinc (Zn) in wheat plants (Triticum aestivum L.). High-resolution elemental imaging with micro-X-ray fluorescence (μ-XRF) was utilized to examine Zn distribution within the vascular bundle of the leaf and whole grains. The inclusion of myo-inositol with Zinc sulfate, significantly increased Zn concentration in shoots in contrast to untreated controls and Zn sulfate applied alone. Foliar Zn treated plants increased Zn in grains by 5-25% with myo-inositol plus Zn treated plants significantly increasing grain Zn concentration compared to both Zn treated and non-treated controls. XRF imaging revealed Zn enrichment in the bran layer and germ, with a very low Zn concentration present in the endosperm. Plants treated with Zn plus myo-inositol showed an enhanced and uniform distribution of Zn throughout the bran layer and germ with an increased concentration in the endosperm. While our data suggest that foliar application of myo-inositol in combination with Zn may be a promising strategy to increase the absorption and mobility of Zn in the plant tissue and subsequently to enhance Zn accumulation in grains, further research is needed to clarify the mechanisms by which myo-inositol affects plant metabolism and nutrient mobility.